2007
DOI: 10.1002/path.2127
|View full text |Cite
|
Sign up to set email alerts
|

Decreased EXT expression and intracellular accumulation of heparan sulphate proteoglycan in osteochondromas and peripheral chondrosarcomas

Abstract: Mutational inactivation of EXT1 or EXT2 is the cause of hereditary multiple osteochondromas. These genes function in heparan sulphate proteoglycan (HSPG) biosynthesis in the Golgi apparatus. Loss of heterozygosity of the EXT1 locus at 8q24 is frequently found in solitary osteochondromas, whereas somatic mutations are rarely found. We investigated the expression of EXT1 and EXT2 (quantitative RT-PCR) and of different HSPGs (immunohistochemistry) in solitary and hereditary osteochondromas and in cases with malig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 58 publications
5
58
1
Order By: Relevance
“…First, the mRNA expression level of EXT1 in osteochondromas is not completely absent, which suggests the presence of cells with functional EXT1 in the tumor. Second, although not significant, the mRNA level of EXT1 seems to increase from low-to high-grade in secondary peripheral chondrosarcomas (Hameetman et al, 2007a). We have also shown that signaling pathways dependent on heparan sulfate, such as fibroblast growth factor and parathyroid hormone-related protein, are inactive in osteochondromas and active in secondary peripheral chondrosarcomas.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…First, the mRNA expression level of EXT1 in osteochondromas is not completely absent, which suggests the presence of cells with functional EXT1 in the tumor. Second, although not significant, the mRNA level of EXT1 seems to increase from low-to high-grade in secondary peripheral chondrosarcomas (Hameetman et al, 2007a). We have also shown that signaling pathways dependent on heparan sulfate, such as fibroblast growth factor and parathyroid hormone-related protein, are inactive in osteochondromas and active in secondary peripheral chondrosarcomas.…”
Section: Discussionmentioning
confidence: 61%
“…The mutation status from 12 cases has been reported previously (Hameetman et al, 2007a). Mutation screening of EXT1 or EXT2 genes was performed and analyzed as described earlier (Hameetman et al, 2007a;Reijnders et al, 2010).…”
Section: Mutation Screeningmentioning
confidence: 99%
“…Recently, we showed that in osteochondromas, heparan sulfate proteoglycans are no longer present at the cell surface but accumulate in the cytoplasm. 36 Therefore, it is possible that the lack of heparan sulfate proteoglycans at the cell surface might influence cell adhesion and motility. The random orientation of the cilium in osteochondromas leads to the assumption that osteochondroma cells have impaired movement (Figure 6b) that may underlie the lack of orientation of the cells, which is a morphological characteristic of this tumor.…”
Section: Cilia In Growth Plate and Osteochondroma Ce De Andrea Et Almentioning
confidence: 99%
“…It was originally hypothesized that EXT1 and EXT2 are tumor suppressor genes, and the loss of heterozygosity (LOH) at these loci plays a key role in osteochondroma formation (8,9). However, the data from genetic analysis of osteochondromas are equivocal (20)(21)(22)(23). It is also uncertain whether osteochondroma is a true neoplasm, which by definition is derived from clonal expansion of progenitor cells, or whether it represents a focal developmental malformation (20).…”
mentioning
confidence: 99%